Hardware developments for the strip detector of the PANDA MVD - Quagli, Tommaso; Justus Liebig University Giessen (My University, 2015)
PANDA is a key experiment of the future FAIR facility, under construction in Darmstadt, Germany. It will study the collisions between an antiproton beam with momenta between 1.5 GeV/c and 15 GeV/c and a fixed proton or nuclear target, allowing to study the QCD at intermediate energies.The Micro Vertex Detector (MVD) is the innermost part of the tracking system of the experiment and its main task is the precise spatial identification of primary and secondary vertices. It will be composed of four concentric barrels and six forward disks, instrumented with silicon hybrid pixel and double-sided silicon microstrip detectors.The work of this thesis is centered on the hardware development of the strip barrel staves. The general concept of the staves is briefly introduced, along with the description of the main sensitive elements and of the carbon fiber mechanical support. The tools and methods for the characterization of strip sensors, with a selection of results from three prototype runs, are presented. The setup designed to study the radiation hardness of the strip sensors has also been used to conduct systematic studies on epitaxial diodes for the pixel part of the MVD. Finally, the last chapter is devoted to the electro-mechanical integration of the barrel staves and describes the developments towards a supporting flexible printed circuit, the validation of the stave cooling system and an extensive evaluation of the powering and cabling scheme of the full MVD.
Hardwareentwicklungen für den Streifendetektor des PANDA MVDs
Keywords: ddc:530